Quality of care for cardiovascular disease prevention in rheumatoid arthritis: compliance with hyperlipidemia screening guidelines. (27th June 2018) - Schmidt, Timothy J; Aviña-Zubieta, J Antonio; Sayre, Eric C; Abrahamowicz, Michal; Esdaile, John M; Lacaille, Diane
Abstract: Objective: To evaluate compliance with hyperlipidaemia screening guidelines for cardiovascular disease prevention in RA compared with the general population. Methods: We conducted a longitudinal study of a population-based RA cohort including all prevalent cases in British Columbia between 1996 and 2006, followed up until 2010, with matched general population controls. Using administrative data, we measured compliance with general population guidelines (testing lipids every 5 years for women ⩾50 and men ⩾40), after excluding individuals with previous diabetes, coronary artery disease or hyperlipidaemia. Compliance was measured as the proportion of 5-year eligibility periods with one or more lipid test. Compliance rates in RA and controls were compared by Chi-square test. Odds ratio (95% CI) of compliance in RA ( vs controls) was estimated using generalized estimating equation models, adjusting for age and sex. Mean compliance rate per patient was also calculated and compared using Mann-Whitney U test. Results: Analyses included 5587 RA individuals and 5613 controls, contributing 6993 and 7208 5-year eligibility periods, respectively. Lipids were measured in 56.6 and 59.5% of eligibility periods in RA and controls, respectively [adjusted odds ratio (95% CI): 0.97 (0.90, 1.06)]. Screening improved over time in RA relative to the general population, but remained suboptimal even after 2003, at 65.8%. Mean (s .d .) compliance rate per patient was 56.6 (47.2)% for RA and 59.5 (46.6)% for controls. Family physicians ordered almost all the lipid tests. Conclusion: Compliance with general population guidelines for hyperlipidaemia screening in RA was poor and did not differ from the general population, despite a higher risk of cardiovascular diseases.